Kajian Penataan Kawasan di Kecamatan Percut Sei Tuan - Sufrial Hendri; Roy Jimmi Tampubolon (Universitas Medan Area, 2023)
Percut Sei Tuan District is one of the sub-districts in Deli Serdang Regency. The position of this sub-district is between Medan City and Batang Kuis District to Kuala Namu Airport. In addition, this sub-district is also one of the centers for the Medindingro development project (Medan - Binjai - Deli Serdang - Karo) as stipulated in RI Presidential Regulation Number 62 of 2011 concerning Medindingro Vision 2027 and is included in the National Strategic Area (KSN).Social and economic problems will arise as the population increases, this requires the development of office facilities, education, health, housing and so on. The challenge is quite complex for the regional government concerned in an effort to build and improve the standard of living and welfare of its people. With the increasing number of activities and dense population, a city can no longer meet the needs of its citizens optimally, so it is necessary to have supporting cities that can accommodate activities that cannot be fulfilled in urban areas. [2] This is done to prevent the development and growth of cities naturally, in other words developing without programmed direction and planning. For this reason, it is necessary to carry out a Study on the Regional Arrangement of Percut Sei Tuan Subdistrict as a guideline for the direction of development for the future, and to avoid uncontrolled forms of development. Creating an integrated urban environment that can increase the efficiency of land use and the carrying capacity of land and can improve the physical quality and appearance of the city.The results of this study are expected to be able to provide directions for regional arrangement in terms of architecture, landscape, regional design in Percut Sei Tuan District, as a guideline for the development and arrangement of urban areas. As a guide for all development actors, both in the design process, space utilization, physical development and in controlling spatial use in Percut Sei Tuan District, Deli Tengah Regency.